1995
DOI: 10.1016/s0022-5223(95)70235-0
|View full text |Cite
|
Sign up to set email alerts
|

Risk analysis and long-term survival in patients undergoing extended resection of locally advanced lung cancer

Abstract: Although locally advanced lung cancer frequently necessitates extended resections to preserve a chance for cure, a higher morbidity is associated with extended resections. It is not known whether the increased morbidity is of relevance for the long-term outcome. It also remains unclear whether exclusion of certain patients according to their risk factors can diminish mortality in these patients. This study therefore investigated whether certain risk factors predispose patients undergoing extended pulmonary res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 34 publications
2
15
0
1
Order By: Relevance
“…If the presence of lymphatic microdissemination reflects a systemic dissemination of the disease, which cannot be cured any more by surgery alone, the group of pN1MM À -patients would benefit from TTE, whereas pN1MM þ -patients would not. In accordance with other studies performed in this field [8,[26][27][28] this would explain the potential benefit of the transthoracic approach even in pN1-patients, when patients were stratified only according to their BER-Ep4 status. This analysis showed significantly improved disease-free survival in the micrometastases-free subset of pooled pN0/pN1-patients when operated on transthoracically as compared to the transhiatal approach.…”
Section: Discussionsupporting
confidence: 86%
“…If the presence of lymphatic microdissemination reflects a systemic dissemination of the disease, which cannot be cured any more by surgery alone, the group of pN1MM À -patients would benefit from TTE, whereas pN1MM þ -patients would not. In accordance with other studies performed in this field [8,[26][27][28] this would explain the potential benefit of the transthoracic approach even in pN1-patients, when patients were stratified only according to their BER-Ep4 status. This analysis showed significantly improved disease-free survival in the micrometastases-free subset of pooled pN0/pN1-patients when operated on transthoracically as compared to the transhiatal approach.…”
Section: Discussionsupporting
confidence: 86%
“…However, evidence suggests that the mortality rate is not significantly increased after extended resections [78] . For example, Izbicki et al [78] showed in patients undergoing extended resection for stage T3 or T4 NSCLC tumors that the study patients with no residual tumor had a 3-year survival rate of 33%.…”
Section: Extended Resections Angioplasty and Marginal Resections Usimentioning
confidence: 99%
“…However, evidence suggests that the mortality rate is not significantly increased after extended resections [78] . For example, Izbicki et al [78] showed in patients undergoing extended resection for stage T3 or T4 NSCLC tumors that the study patients with no residual tumor had a 3-year survival rate of 33%. In addition, Spaggiari et al [79] reported a 3-year probability of survival of 39% after extended pneumonectomy with partial resection of the left atrium for advanced lung cancer.…”
Section: Extended Resections Angioplasty and Marginal Resections Usimentioning
confidence: 99%
“…In many previous studies, survival extension was shown in a selected group of T4 NSCLC patients who had been operated on (Watanabe et al, 1991;Martini et al, 1994;Izbicki et al, 1995;Bernard et al, 2001;Osaki et al, 2003;Pitz et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…For example, whether the treatment is curative or palliative, T4 diagnosis, the state of lymph nodes, the pathological subgroup type of the tumor, the age at diagnosis, smoking status, co-morbidity, ECOG-PS (Eastern Cooperative Oncology Group Performance Status), and weight loss can all be factors that affect treatment results and survival rates (Watanabe et al, 1991;Martini et al, 1994;Izbicki et al 1995;Bernard et al, 2001;Osaki et al, 2003;Pitz et al, 2003;Gregory et al, 2012). Therefore it is important to identify the factors that affect overall survival (OS) rate and event free survival (EFS) rates for the selection of treatments and differentiation of patients in this heterogeneous group of LA-NSCLC (T4 N0-3 M0) cases.…”
Section: Introductionmentioning
confidence: 99%